Farmers' Response Towards Technological Interventions Under Assessment and Refinement - Singh, R. K.; Dubey, S. K.; Ratan, R. P. Singh; Gupta, D. Das (Indian Journal of Extension Education, 2013)
Farmers' responses towards technology assessment and refinment were sutdied in five villages of Karge panchayat of  Mandar block in Ranchi District of Jharkhand. Results revealed that all the intervened technologies assessed by the  farmers' were agro-climatically more suitable, more profitable and more compatible, which contributed to their overall  appropriateness in comparison to the corresponding farmers' practices. Overall reaction of the respondents on intervened  technologies was found to be positive in terms of selected attributes i.e. socio-cultural compatibility, compatibility with  existing farming system components, divisibility of technology, simplicity, compatibility with internal resources of the  households, element of risk involved and visibility except their easy availability in the local markets. Majority of the  farmers' felt difficulties in accepting the recommended technologies as such in respect of most of the intervened  technologies and preferred the refined technologies which were suitable in their agro-ecological situation and socio economic condition.
Keywords: Farmers' response; technological interventions; farming system; assessment and refinement